A robust Beveridge-Nelson decomposition using a score-driven approach with an application - Francisco Blasques; Janneke van Brummelen; Paolo Gorgi; Siem Jan Koopman (Tinbergen Institute, 2024)
The equivalence of the Beveridge-Nelson decomposition and the trend-cycle decomposition is well established. In this paper we argue that this equivalence is almost immediate when a Gaussian score-driven location model is considered. We also provide a natural extension towards heavy-tailed distributions for the disturbances which lead to a robust version of the Beveridge-Nelson decomposition.
Keywords: C22; E32; 330; trend and cycle; filtering; autoregressive integrated moving average model; score-driven model; heavy-tailed distributions